An Accurate Upper Lid Blepharoplasty: A Key Component of Facial Rejuvenation - Zimmerman, Zachary; Thomas, James Regan (Facial Plastic Surgery, 2021)
Upper eyelid surgery is a common procedure performed by a variety of subspecialists including facial plastic surgeons, oculoplastic surgeons, general otolaryngologists, and plastic surgeons. Traditionally, a skin incision is marked in the preoperative setting to allow for an excision that eliminates upper eyelid hooding while preventing lagophthalmos. Many different methodologies have been proposed to maximize results and minimize complications. In this article, the authors propose a unique way to safely and effectively address dermatochalasis. The pinch technique allows for an accurate assessment of excess skin and provides a method that requires less operative time than traditional techniques. The use of both local anesthetic with epinephrine and hyaluronidase helps achieve the appropriate plane and attain better hemostasis. Importantly, the presented technique allows for reassessment and revision of the amount of skin excision before incision creation. It is a useful methodology for any surgeon performing upper lid blepharoplasty.
Keywords: upper eyelid surgery; blepharoplasty; aging face